PROJECT MANAGEMENT OF DIGITAL BUILDING ENERGY MONITORING SYSTEMS BASED ON A DIGITAL TWIN (International journal of artificial intelligence, 2026)
This article examines project management of digital building energy monitoring systems based on the digital twin concept. A mathematical model for calculating the actual energy efficiency of a building, including baseline household consumption, is proposed. Unlike approaches prevailing in the scientific literature, the proposed model is designed for the operation of a digital twin without the mandatory use of BIM models and IoT infrastructure, significantly expanding its applicability to a wide range of existing buildings.